Policy Tools for Addressing Urban Sprawl: Urban Growth Boundaries - Eric J. STRAUSS; Bogdana NEAMŢU (Transylvanian Review of Administrative Sciences, 2006)
The analysis herein explores the topic of urban growth boundaries and how local governments in Romania could use this growth management tool in order to address unplanned, haphazard growth that is taking place at the fringe of cities and in the villages/ farming communities that surround them. The structure of the paper is threefold. The first section focuses on a brief socio-economic profile of Cluj-Napoca, Romania. The aim is to provide a better context and facilitate the reader’s understanding of the nature of urban growth and suburbanization in Romania. Cluj-Napoca is currently in the process of adopting a master plan for the city and specific policy recommendations on how to address urban sprawl may prove useful. The authors hope to stir a debate among scholars, practitioners, and residents with regard to how the city of Cluj will further develop and whether future development should occur in the same manner it occurred during the last 10 years. The second section of the paper is meant to introduce the concepts of growth management and urban growth boundaries. The former is described in terms of a planning philosophy while the latter is portrayed as a specific policy tool that growth management advocates suggest it could be used in order to fight sprawl. A case study on urban growth boundaries is presented in order to underscore specific advantages and disadvantages associated with establishing a growth boundary. The last section comprises several preliminary policy recommendations for the city of Cluj-Napoca. Because of the incomplete data the authors currently have on critical issues some of the recommendations are general in scope and need to be further detailed.